Oxidation‐Enhanced Piezocatalytic Activity in Carbon Nitride‐Based Catalysts for Hydrogen and Hydrogen Peroxide Production - Pan, Ying; Liao, Luocheng; Zhang, Xinwen; Liu, Yunya; Su, Ran; Lopez Salas, Nieves (ChemSusChem)
Driven by the urgent need for a green, safe, and cost‐effective approach to producing H 2 and H 2 O 2 —both highly valuable in green energy and environmental protection fields—piezocatalysis, which converts mechanical energy into valuable chemicals, has emerged as a promising solution. However, current catalyst systems face challenges due to the need for materials with both a strong piezoelectric effect and favorable catalytic activity. Herein, the construction of an oxidized carbon nitride ( g ‐C 3 N 4 ) matrix anchored with TiO 2 nanoparticles via alkaline hydrothermal treatment is reported. Under ultrasonication, the g ‐C 3 N 4 /TiO 2 composite exhibits optimal performance under carefully controlled alkaline hydrothermal conditions. With a low concentration of Ba(OH) 2 during hydrothermal treatment, Ba(OH) 2 provides an alkaline medium, oxidizing the g ‐C 3 N 4 species and introducing structural defects into the g ‐C 3 N 4 framework. The disruption of the g ‐C 3 N 4 matrix, along with its interaction with TiO 2 nanoparticles, enhances the piezoelectric effect. Consequently, the oxidized g ‐C 3 N 4 /TiO 2 composite achieves a remarkable H 2 production rate of 4427.2 μmol g −1 and an H 2 O 2 production rate of 809.3 μmol g −1 within 1 h without the addition of any sacrificial agents or cocatalysts. This work presents an effective strategy for the structural optimization of g ‐C 3 N 4 ‐based materials and may inspire new approaches for designing advanced piezocatalysts.

Engineering Charge Polarized Au Sites for Low‐Temperature Acetylene Hydrochlorination - Li, Chun; Liu, Ruoting; Zhang, Zilong; Zuo, Fangmin; Jiang, Tingting; Zhang, Haifeng; Wang, Bolin; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Abstract Cationic gold catalyzed acetylene hydrochlorination represents a classical landmark in eliminating global mercury pollution, but their sustainable implementation is hindered by acetylene‐dependence design criteria and high operating temperatures. Herein, a platform of carbon‐supported single‐atoms Au catalysts (Au/BC and Au/NC) with polarized charge characteristics are developed via engineering Au sites with hosted B, N configurations. The negatively charged Au/BC catalyst unlocks the low‐temperature inactivity (413–423K) of the Au/NC catalyst while exhibiting superior catalytic performance in the 433–473K operating temperature range. We confirm that the classical scaling relationships on acetylene can be broken by narrowing the adsorption capacity between acetylene and HCl on Au δ⁻ sites via facilitating the back‐donation of d electrons into the antibonding orbitals of acetylene. Prolonging the durability of Au catalysts is achieved through preceding an additional robust Au δ⁻ → Au δ⁺ cycle prior to the classic Au δ⁺ → Au 0 route. This work opens a promising avenue for low temperature vinyl chloride production.

Adenine and D‐Ribose Coderived Activated Carbon with N‐Methyl‐2‐Pyrrolidone‐Modified Aqueous Electrolyte for Long‐Life Zinc‐Ion Capacitors - Tao, Li; Li, Chun; Lu, Xuejun; Mir, Rameez Ahmad; Lopez Salas, Nieves; Liu, Jian (Batteries & Supercaps)
Aqueous zinc (Zn)‐ion capacitors (AZICs) have addressed considerable attention due to their high energy density, low toxicity, and rich abundance of Zn metal. However, the development of ultra‐long cycle life and high energy density AZICs is often hindered by the lack of adequately optimized active carbon (AC) electrodes and compatible electrolytes. Herein, high‐performance, free‐standing AC electrodes for AZICs are derived from sustainable precursors—adenine and D‐ribose—using magnesium chloride hexahydrate as an activation agent via a eutectic template strategy. Furthermore, an aqueous hybrid electrolyte tailored to the designed AC electrodes is developed, significantly enhancing the stability and cycle life of AZICs. The resulting AZIC achieves a high specific capacity of 164.39 F g −1 at 0.1 A g −1 and a magnificently long cell life of over 50 000 cycles with nearly 94.5% capacitance retention at 10 000 th cycles, and 76.3% at 50 000 th cycle. The pouch cell assembly also demonstrates comparable specific capacitance and energy density to the coin cell, underscoring the potential of large‐scale applications of AZICs.

Interfacial engineering of CuSe2/FeSe2 heterojunctions for water splitting: a pathway to high-performance hydrogen and oxygen evolution reactions - Kumari, Sandhyawasini; Pahra, Swapna; Tripathy, Amrita; Sumanth, N.; Lopez Salas, Nieves; Tiwari, Santosh K.; Khan, Afaq Ahmad; Devi, Pooja; Santosh, M. S. (Nanoscale)
Enhanced bifunctional electrocatalysis via CuSe 2 /FeSe 2 heterojunctions for efficient water splitting was achieved.

Heteroatom co-doped green pea peel-derived biochar for high-performance energy storage applications - Makinde, Wasiu Olakunle; Hassan, Mohsen A.; Semida, Wael M.; Pan, Ying; Guan, Guoqing; Lopez Salas, Nieves; Khalil, Ahmed S. G. (RSC Advances)
Green pea peel (GPP) is a waste, and it is abundant and available to be used for biochar synthesis.

Fe and Sn Single-Site-Based Electrodes for High-Current CO2 Reduction in Acid Media and Stable Zn–CO2 Batteries - Hu, Jiajun; Goberna-Ferrón, Sara; Simonelli, Laura; Lopez Salas, Nieves; García, Hermenegildo; Albero, Josep (ACS Applied Energy Materials)

Understanding the Wettability of C1N1 (Sub)Nanopores: Implications for Porous Carbonaceous Electrodes - Lamata‐Bermejo, Irene; Keil, Waldemar; Nolkemper, Karlo; Heske, Julian; Kossmann, Janina; Elgabarty, Hossam; Wortmann, Martin; Chorążewski, Mirosław; Schmidt, Claudia; Kühne, Thomas D.; Lopez Salas, Nieves; Odziomek, Mateusz (Angewandte Chemie International Edition)
Abstract Understanding how water interacts with nanopores of carbonaceous electrodes is crucial for energy storage and conversion applications. A high surface area of carbonaceous materials does not necessarily need to translate to a high electrolyte‐solid interface area. Herein, we study the interaction of water with nanoporous C 1 N 1 materials to explain their very low specific capacitance in aqueous electrolytes despite their high surface area. Water was used to probe chemical environments, provided by pores of different sizes, in 1 H MAS NMR experiments. We observe that regardless of their high hydrophilicity, only a negligible portion of water can enter the nanopores of C 1 N 1 , in contrast to a reference pure carbon material with a similar pore structure. The common paradigm that water easily enters hydrophilic pores does not apply to C 1 N 1 nanopores below a few nanometers. Calorimetric and sorption experiments demonstrated strong water adsorption on the C 1 N 1 surface, which restricts water mobility across the interface and impedes its penetration into the nanopores.

35 challenges in materials science being tackled by PIs under 35(ish) in 2024 - Lázaro, Isabel Abánades; Anastasaki, Athina; Ardoña, Herdeline Ann M.; Arguilla, Maxx Q.; Bati, Abdulaziz S.R.; Batmunkh, Munkhbayar; Besford, Quinn A.; Browne, Michelle P.; Bryant, Saffron J.; Carlotti, Marco; Contini, Claudia; Delaney, Colm; et al. (Matter)

Template‐Induced Graphitic Nanodomains in Nitrogen‐Doped Carbons Enable High‐Performance Sodium‐Ion Capacitors - Li, Chun; Song, Zihan; Liu, Minliang; Lepre, Enrico; Antonietti, Markus; Zhu, Junwu; Liu, Jian; Fu, Yongsheng; Lopez Salas, Nieves (ENERGY & ENVIRONMENTAL MATERIALS)
Sodium‐ion capacitors (SICs) have great potential in energy storage due to their low cost, the abundance of Na, and the potential to deliver high energy and power simultaneously. This article demonstrates a template‐assisted method to induce graphitic nanodomains and micro‐mesopores into nitrogen‐doped carbons. This study elucidates that these graphitic nanodomains are beneficial for Na + storage. The obtained N‐doped carbon (As8Mg) electrode achieved a reversible capacity of 254 mA h g −1 at 0.1 A g −1 . Moreover, the As8Mg‐based SIC device achieves high combinations of power/energy densities (53 W kg −1 at 224 Wh kg −1 and 10 410 W kg −1 at 51 Wh kg −1 ) with outstanding cycle stability (99.7% retention over 600 cycles at 0.2 A g −1 ). Our findings provide insights into optimizing carbon's microstructure to boost sodium storage in the pseudocapacitive mode.

Synergistic design of high-performance symmetric supercapacitor based on iron oxide nanoplatelets/COOH-MWCNTs heterostructures: DFT computation and experimental analysis - Mohamed, Sayed R.E.; Mohammed, Ahmed S.A.; Metwalli, Ossama I.; El-Sayed, S.; Khabiri, Gomaa; Hassan, Abdelwahab; Yin, Kai; Abdellatif, Sameh O.; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Journal of Alloys and Compounds)

Crystal engineering and sorption studies on CN- and dipyridyl-bridged 2D coordination polymers - Nguepmeni Eloundou, Valoise Brenda; Kenfack Tsobnang, Patrice; Kamgaing, Theophile; Gogoi, Chiranjib; Lopez Salas, Nieves; Bourne, Susan A. (CrystEngComm)
Structure–property relationships were studied in two coordination polymers {[Ni(bpe)(H 2 O) 2 ][Ni(CN) 4 ]·2 H 2 O} n and {[Cu(bpe)(H 2 O) 2 ][Ni(CN) 4 ]·ethanol} n . We show that the length of the ligand does not control the synthesis of Hofmann-type polymers.

Value-added utilization of biowaste-derived lignin towards the synthesis of oxygen-enriched hierarchical laser-induced graphene and its application as a micro-supercapacitor - Katwesigye, Samuel; El-Khouly, Mohamed E.; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Journal of Energy Storage)

Sulfur and nitrogen co-doping of peanut shell-derived biochar for sustainable supercapacitor applications - Makinde, Wasiu Olakunle; Hassan, Mohsen A.; Pan, Ying; Guan, Guoqing; Lopez Salas, Nieves; Khalil, Ahmed S.G. (Journal of Alloys and Compounds)

Revisiting the phosphonium salt chemistry for P-doped carbon synthesis: toward high phosphorus contents and beyond the phosphate environment - André, Rémi F.; Gervais, Christel; Zschiesche, Hannes; Jianu, Teodor; Lopez Salas, Nieves; Antonietti, Markus; Odziomek, Mateusz (Materials Horizons)
Calcination of THPC–urea in metal chloride hydrate salt affords porous P/N-doped carbonaceous materials (up to 18 wt% [P]), used as oxidative dehydrogenation catalysts.

Novel onion flower-derived biochar for high-performance sustainable supercapacitor applications - Kwarteng, Felix A.; Abdel-Aty, Ahmed A.R.; Mohamed, Sayed R.E.; Hassan, Mohsen A.; Ohashi, Hidenori; Lopez Salas, Nieves; Semida, Wael M.; Khalil, Ahmed S.G. (Diamond and Related Materials)

Green Light Photoelectrocatalysis with Sulfur‐Doped Carbon Nitride: Using Triazole‐Purpald for Enhanced Benzylamine Oxidation and Oxygen Evolution Reactions - Jerigova, Maria; Markushyna, Yevheniia; Teixeira, Ivo F.; Badamdorj, Bolortuya; Isaacs, Mark; Cruz, Daniel; Lauermann, Iver; Muñoz‐Márquez, Miguel Ángel; Tarakina, Nadezda V.; Lopez Salas, Nieves; Savateev, Oleksandr; Jimenéz‐Calvo, Pablo (Advanced Science)
Abstract Materials dictate carbon neutral industrial chemical processes. Visible‐light photoelectrocatalysts from abundant resources will play a key role in exploiting solar irradiation. Anionic doping via pre‐organization of precursors and further co‐polymerization creates tuneable semiconductors. Triazole derivative‐purpald, an unexplored precursor with sulfur (S) container, combined in different initial ratios with melamine during one solid‐state polycondensation with two thermal steps yields hybrid S‐doped carbon nitrides (C 3 N 4 ). The series of S‐doped/C 3 N 4 ‐based materials show enhanced optical, electronic, structural, textural, and morphological properties and exhibit higher performance in organic benzylamine photooxidation, oxygen evolution, and similar energy storage (capacitor brief investigation). 50M‐50P exhibits the highest photooxidation conversion (84 ± 3%) of benzylamine to imine at 535 nm – green light for 48 h, due to a discrete shoulder (≈700) nm, high sulfur content, preservation of crystal size, new intraband energy states, structural defects by layer distortion, and 10–16 nm pores with arbitrary depth. This work innovates by studying the concomitant relationships between: 1) the precursor decomposition while C 3 N 4 is formed, 2) the insertion of S impurities, 3) the S‐doped C 3 N 4 property‐activity relationships, and 4) combinatorial surface, bulk, structural, optical, and electronic characterization analysis. This work contributes to the development of disordered long‐visible‐light photocatalysts for solar energy conversion and storage.

Tin (II) Chloride Salt Melts as Non‐Innocent Solvents for the Synthesis of Low‐Temperature Nanoporous Oxo‐Carbons for Nitrate Electrochemical Hydrogenation - Zheng, Xinyue; Tian, Zhihong; Bouchal, Roza; Antonietti, Markus; Lopez Salas, Nieves; Odziomek, Mateusz (Advanced Materials)
Abstract Carbonaceous electrocatalysts offer advantages over metal‐based counterparts, being cost‐effective, sustainable, and electrochemically stable. Their high surface area increases reaction kinetics, making them valuable for environmental applications involving contaminant removal. However, their rational synthesis is challenging due to the applied high temperatures and activation steps, leading to disordered materials with limited control over doping. Here, a new synthetic pathway using carbon oxide precursors and tin chloride as a p‐block metal salt melt is presented. As a result, highly porous oxygen‐rich carbon sheets (with a surface area of 1600 m 2 g −1 ) are obtained at relatively low temperatures (400 °C). Mechanistic studies reveal that Sn(II) triggers reductive deoxygenation and concomitant condensation/cross‐linking, facilitated by the Sn(II) → Sn(IV) transition. Due to their significant surface area and oxygen doping, these materials demonstrate exceptional electrocatalytic activity in the nitrate‐to‐ammonia conversion, with an ammonia yield rate of 221 mmol g −1 h −1 and a Faradic efficiency of 93%. These results surpass those of other carbon‐based electrocatalysts. In situ Raman studies reveal that the reaction occurs through electrochemical hydrogenation, where active hydrogen is provided by water reduction. This work contributes to the development of carbonaceous electrocatalysts with enhanced performance for sustainable environmental applications.

Oxygen‐Rich Carbon Nitrides from an Eutectic Template Strategy Stabilize Ni, Fe Nanosites for Electrocatalytic Oxygen Evolution - Li, Chun; Lepre, Enrico; Bi, Min; Antonietti, Markus; Zhu, Junwu; Fu, Yongsheng; Lopez Salas, Nieves (Advanced Science)
Abstract Functionalized porous carbons are central to various important applications such as energy storage and conversion. Here, a simple synthetic route to prepare oxygen‐rich carbon nitrides (CNOs) decorated with stable Ni and Fe‐nanosites is demonstrated. The CNOs are prepared via a salt templating method using ribose and adenine as precursors and CaCl 2 ·2H 2 O as a template. The formation of supramolecular eutectic complexes between CaCl 2 ·2H 2 O and ribose at relatively low temperatures facilitates the formation of a homogeneous starting mixture, promotes the condensation of ribose through the dehydrating effect of CaCl 2 ·2H 2 O to covalent frameworks, and finally generates homogeneous CNOs. As a specific of the recipe, the condensation of the precursors at higher temperatures and the removal of water promotes the recrystallization of CaCl 2 ( T < T m = 772 °C), which then acts as a hard porogen. Due to salt catalysis, CNOs with oxygen and nitrogen contents as high as 12 and 20 wt%, respectively, can be obtained, while heteroatom content stayed about unchanged even at higher temperatures of synthesis, pointing to the extraordinarily high stability of the materials. After decorating Ni and Fe‐nanosites onto the CNOs, the materials exhibit high activity and stability for electrochemical oxygen evolution reaction with an overpotential of 351 mV.

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons - Li, Jiaxin; Kossmann, Janina; Zeng, Ke; Zhang, Kun; Wang, Bingjie; Weinberger, Christian; Antonietti, Markus; Odziomek, Mateusz; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Abstract Self‐templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m 2 g −1 ) originating from low activity of metal cations (e.g., K + or Na + ) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo‐carbons with large SSA of the order of 3000 m 2 g −1 , pore volume approaching 2 cm 3 g −1 , tunable oxygen contents, and yields of up to 15 %. We unravel the role of Cs + as an efficient promoter of framework formation, templating and etching agent, while acetates act as carbon/oxygen sources of carbonaceous frameworks. The oxo‐carbons show record‐high CO 2 uptake of 8.71 mmol g −1 and an ultimate specific capacitance of 313 F g −1 in the supercapacitor. This study helps to understand and rationally tailor the materials design by a still rare organic solid‐state chemistry.

Template-induced graphitic nanodomains in nitrogen-doped carbons enable high-performance sodium-ion capacitors - ACCEPTED MANUSCRIPT - Lopez Salas, Nieves; Li, Chun; Song, Zihan; Liu, Minliang; Lepre, Enrico; Antonietti, Markus; Zhu, Junwu; Liu, Jian; Fu, Yongsheng
Sodium-ion capacitors (SICs) have great potential in energy storage due to their low cost, the abundance of Na, and the potential to deliver high energy and power simultaneously. This paper demonstrates a template-assisted method to induce graphitic nanodomains and micro-mesopores into nitrogen-doped carbons. This study elucidates that these graphitic nanodomains are beneficial for Na+ storage. The obtained N-doped carbon (As8Mg) electrode achieved a reversible capacity of 254 mA h g−1 at 0.1 A g−1. Moreover, the As8Mg-based SIC device achieves high combinations of power/energy densities (52 W kg−1 at 204 Wh kg−1 and 10,456 W kg−1 at 51 Wh kg−1) with outstanding cycle stability (99.7% retention over 10000 cycles at 0.2 A g−1). Our findings provide insights into optimizing carbon’s microstructure to boost sodium storage in the pseudo-capacitive mode.
Keywords: sodium ion capacitor; anode; template; N-doped carbons; graphitic nanodomains